Biochar and Nitrogen Fertilizers Effects on Growth and Flowering of Garland Chrysanthemum (Chrysanthemum Coronarium L.) Plant - Ali, Mariwan A.; Mjeed, Ardalan J. (Kurdistan Journal of Applied Research, 2017)
This experiment was conducted to study the effect two types of biochar and nitrogen fertilizers amendment, with different rates on morphological attributed of garland chrysanthemum plant. Two different types of biochar (BT) Eucalyptus biochar (EB), and Salix biochar (SB), four biochar rates- BR (at 0, 1, 2 and 3%), and three rates of nitrogen fertilizer- NR (0, 140 and 280 mg kg-1) with three replications on plant growth were used in this research. The (Chrysanthemum coronarium L.) was used as a test plant to study some morphological characters including: Plant Height (PH) cm, Fresh Weight Per Plant (FWP) g, Number of Leaves Per Plant (NLP), Stem Diameter (SD) cm, Flower Diameter (FD), Number of Flower Per Plant (NFP) and Number of Flower Bud Per Plant (NFBP) cm. The Double Barrel Design was used for making biochar by pyrolysis system. The experiment was conducted in the plastic house condition. The results showed that biochar applications at a rate of 3%, significantly increase PH, FWP, NLP, SD, FD, and NFBP, while NFP increased only at 2% biochar application and decrease at the 3% rate. The application of 280 mg kg-1 of nitrogen significantly increased all of the parameters. The plant grown in the soils amended with the EB were higher than grown in the soils of the SB. In addition, the best value in the study was observed were biochar combined with nitrogen fertilizers.